Insecurity in the South East and its Possible Solutions: using Anambra State Nigeria as a Focus, 1999-2023 - Gloria Chinyere Chukwujama (Indonesian Journal of Character Education Studies, 2024)
Background: The South-East region of Nigeria, particularly Anambra State, has been facing a series of escalating security challenges since 1999. These issues have significantly hampered socio-economic development and posed threats to the lives and well-being of residents. Insecurity-marked by violence, kidnappings, political unrest, and social instability-remains the most critical among these challenges. Objective: This study aims to examine the causes and effects of insecurity in the South-East, with Anambra State as the focal point, and to propose possible solutions to mitigate the crisis. Method: The study employed a descriptive survey design and was conducted in Anambra State between 1999 and 2023. Data were collected through interviews and a validated questionnaire titled “The Causes of Insecurity, Effect, and Its Possible Solutions in the South-East and in Anambra State in Particular.” The respondents were randomly selected youths from the state. A combination of multivariate regression methods and statistical inference techniques was used to analyze the data. Result: The analysis revealed that multiple factors contribute to insecurity in Anambra State, including youth unemployment, political marginalization, poor governance, and the activities of non-state actors. The data also showed that insecurity has profound effects on economic development, education, and daily life. The findings underscore the urgent need for a multi-sectoral approach to address these issues. Conclusion: Insecurity in the South-East, especially in Anambra State, is a complex, multifaceted issue requiring immediate and sustained interventions. Understanding its root causes is crucial to devising effective and lasting solutions. Contribution: The findings of this study provide relevant insights for policymakers, civil society actors, and especially Nigerian youths, emphasizing their role in fostering peace and development. The study also offers a foundation for further research on regional insecurity and strategic interventions.